PENGARUH PELATIHAN KESIAPSIAGAAN BENCANA TERHADAP PENINGKATAN PENGETAHUAN TENTANG KIT KESEHATAN REPRODUKSI PADA TANGGAP DARURAT BENCANA - Mahdalena Prihatin Ningsih; Nurul Aziza Ath Thaariq; Lisa Rahmawati (Jurnal Medikes (Media Informasi Kesehatan), 2023)
Disasters not only have an impact on health in general but also affect reproductive health Disasters caused obstructed access to reproductive health services, damaged health facilities, and limited access to contraception thereby increasing the number of unwanted pregnancies, increasing the risk of rape, sexual abuse, and exploitation, and the incidence of STIs and HIV will increase. West Sumatra is one of the provinces in Indonesia which is prone to disasters and is a high-risk area known as the red zone for disasters. The high Disaster Risk Index encourages the government to pay attention to disaster management and disaster preparedness. However, the issue of reproductive health services during emergencies is often neglected. The purpose of this study was to determine the effect of disaster preparedness training on increasing knowledge about reproductive health kits in disaster emergency response. The type of research used was a quasi-experimental study with a one-group pretest-posttest research design. This study used a group that was given an intervention in the form of disaster preparedness training. The sampling technique was purposive sampling with a total of 58 respondents. Data processing using paired T-test. The average value before being given disaster preparedness training was 15.90 and after being given training it increased to 21.34, which means that there was an increase in the average knowledge score of 5.44 with a p-value = 0.000. It can be concluded that the effect of disaster preparedness training affects increasing knowledge about reproductive health kits in disaster emergency response.